การวิเคราะห์ทัศนมิติและกระบวนการถ่ายทอดดนตรีไทย ของครูชนก สาคริก AN ANALYSIS OF CHANOK SAGARIK’S PERSPECTIVES AND THAI MUSICAL TRANSMISSION METHODS - เสียงประเสริฐ, ปพิชญา; อุทัยสุข, ดนีญา (An Online Journal of Education, 2014)
การวิจัยในครั้งนี้ มีวัตถุประสงค์ คือ 1) ศึกษาประวัติและความเป็นตัวตนของครูชนก สาคริก 2) วิเคราะห์ทัศนมิติและกระบวนการถ่ายทอดดนตรีไทยของครูชนก สาคริก โดยใช้ระเบียบวิธีวิจัยเชิงคุณภาพ รวบรวมข้อมูลจากเอกสาร บทความ การสัมภาษณ์ วิเคราะห์ข้อมูลด้วยวิธีการตีความ สร้างข้อสรุปแบบอุปนัยและนำเสนอเป็นความเรียง ผลการวิจัย พบว่า 1) ครูชนก สาคริกเป็นผู้สืบทอดสายตระกูล ศิลปบรรเลงและได้รับการปลูกฝังด้านการสอนและคุณธรรมจากครอบครัว ส่งผลให้ครูชนก สาคริก มีบุคลิก ความสนใจและความเป็นครูที่เป็นเอกลักษณ์ 2) ทัศนมิติและกระบวนการถ่ายทอดดนตรีไทยของครูชนก สาคริก แบ่งออกเป็น 3 ด้าน คือ ด้านการปฏิบัติตน ได้แก่ การทำงานให้เต็มที่และดีที่สุด ทำโดยไม่หวังผลและทำเพื่อประโยชน์ส่วนรวม มีกระบวนการ คือ ประพฤติตนเป็นแบบอย่าง เผยแพร่ดนตรี สู่สาธารณะ ผลิตสื่อออนไลน์ เผยแพร่ธรรมะและก่อตั้งมูลนิธิหลวงประดิษฐไพเราะ ด้านการสอน แบ่งเป็น การอนุรักษ์ คือ ปลูกฝังดนตรีไทยให้กับเด็ก รักษาภูมิปัญญาของคนรุ่นก่อนและรักษาระเบียบจารีตที่เป็นมา โดยใช้กระบวนการ จัดทำการ์ตูนดนตรีไทย อนุรักษ์ทางเพลงของครูหลวงประดิษฐไพเราะ อนุรักษ์ระบบโน้ตตัวเลข 9 ตัวและจัดพิธีไหว้ครู และการพัฒนา คือ การเปลี่ยนวิธีการนำเสนอดนตรีไทยสู่สังคม เผยแพร่ผ่านสื่อและเทคโนโลยี โดยประยุกต์เครื่องดนตรีอื่นๆ มาบรรเลงเพลงไทย พัฒนาสื่อการเรียนการสอนด้วยเทคโนโลยี พัฒนาเทคนิคและวิธีสอน ประพันธ์เพลงและพัฒนาตำรา บทความและเอกสารต่างๆ ด้านการพัฒนาผู้เรียนให้เป็นคนเก่ง ดีและเรียนรู้ดนตรีไทยอย่างมีความสุข ให้เก่ง โดย ใช้วิธีการสอนและสื่อที่หลากหลายและเหมาะสมกับผู้เรียน และฝึกให้ผู้เรียนมีกระบวนการคิดและถ่ายทอดได้ ให้ดี โดย การสอดแทรกมารยาท คุณธรรม คุณค่าของดนตรีและวัฒนธรรม ให้มีความสุข โดยเน้นให้ผู้เรียนสนุก ผ่อนคลาย อบอุ่นและผูกพัน เน้นความรักความเข้าใจ และเปิดโอกาสให้นักเรียนแสดงออกอย่างเท่าเทียมกัน The objectives of the present study are 1) to study the background and identity of Chanok Sagarik, and 2) to analyze perspectives and the Thai musical transmission methods of Chanok Sagarik by qualitative research with data collected from documents, articles and interviews. The data were interpreted, inferentially concluded and presented in written form. The results are that 1) Chanok Sagarik was a descendant of the Silpabanleng family and was passed on the tradition of teaching and sense of morality from his family. This gave Chanok Sagarik a unique personality, interest and teaching style. 2) The perspectives and Thai musical transmission methods of Chanok Sagarik are divided into 3 parts. First is behavior, which refers to dedication, doing one’s best in work without expecting anything in return and living in a socially responsible manner. For him, the process involved being a role model, promoting music, producing online materials, practicing Dharma, and establishing the Luangpraditphairor Foundation. Second is teaching which is divided into conservation i.e. passing on Thai music to children, preserving the past generations’ knowledge and customs by creating Thai musical cartoons, conserving Luangpraditphairor’s songs and the nine-musical note system, and organizing the Wai Khru (paying respect to teachers) ceremony. The other aspect of teaching is development by changing the way to present Thai music to society through media and technology by adapting other musical instruments for Thai songs, developing teaching materials with technology, developing techniques and teaching styles, writing songs, and developing textbooks, articles and documents. Third is developing competent, good and happy Thai musical instrument learners. Competent students are developed by combining different teaching styles using a variety of materials appropriate for the learners. These train students to master the understanding and pass on their knowledge. Good students are developed by teaching manners, morality, and appreciation of the value of music and culture. Happy students are developed by emphasizing the learner’s enjoyment, relaxation, warmth, and attachment. Also, Chanok Sagarik focuses on love and understanding and giving students equal opportunities to express themselves.